A clash of kings - Martin, George R. R. (Martin, George R. R. Song of ice and fire, 2011)
"Six factions struggle for control of a divided land and the Iron Throne of the Seven Kingdoms, preparing to stake their claims through tempest, turmoil, and war ... Against a backdrop of incest and fratricide, alchemy and murder, victory may go to the men and women possessed of the coldest steel--and the coldest hearts. For when kings clash, the whole land trembles."